Synthesis of novel hexahydroquinolines and evaluation of their antibacterial effects on bacteria inducing skin wound infections, accompanied by quantum mechanical calculations - Fateme Khojaste; Nahid Shajari; Parvin Eskandari; Mohammad Reza Farahpour; Hooriye Yahyaei (Results in Chemistry)
This study aims to synthesize new hexahydroquinolines using N-aminophthalimide and investigate their properties on bacteria that cause infection in cutaneous wounds. For this purpose, a one-pot multicomponent reaction involving N-aminophthalimide, dimedone, malononitrile, and aromatic aldehydes in ethanol solvent and at room temperature using small amounts of zirconium oxynitrate hydrate (ZrO(NO3)2.2H2O) and triethylamine catalysts was used, and the effect of the obtained products on Staphylococcus aureus, Pseudomonas aeruginosa, Staphylococcus epidermidis, Klebsiella pneumoniae, Escherichia coli, and Stenobacter baumannii was investigated. FT-IR, 1H NMR, 13C NMR, and elemental analysis were used to confirm the structure of the products. The results of the well diffusion test determined that the obtained products did not show any antibacterial activity against bacteria, but in MIC and MBC tests, the synthesized compounds showed higher antibacterial activity than antibiotics. In this way, the antibacterial properties of the desired compounds were successfully investigated and confirmed.Density Functional Theory (DFT) was utilized to perform quantum theoretical calculations for six structures of hexahydroquinoline derivatives. For these derivatives in the ground state, chemical shift calculations and FT-IR spectroscopy data for 1H NMR and 13C NMR were computed and compared with experimental results. Theoretical computations were conducted to analyze the frontier molecular orbitals and thermodynamic characteristics of the derivatives.DFT calculations (B3LYP/6–311 + G**) corroborated experimental data, showing <3 % deviation in IR frequencies and strong correlation for NMR chemical shifts (R2 > 0.98). Frontier molecular orbital analysis identified compound 5 f as the most stable (HOMO-LUMO gap = 0.0787 eV) and least reactive, consistent with its superior antibacterial performance. These results demonstrate the dual utility of combined synthesis and computational modeling in developing heterocyclic antibiotics. The results indicated a strong agreement between the theoretical and experimental findings.